Peranan Literasi Wirausaha, Literasi Digital dan Pengalaman Keluarga dalam Mendukung Minat Wirausaha di Kalangan Mahasiswa - Mutinda Teguh Widayanto; Raihan Wishal Nafis; Angel Agus Trifanto; Kamilah Kamilah (Fakultas Ekonomi Universitas Panca Marga, 2023)
The purpose of this research is to analyze the factors that can support entrepreneurial interest among students. This is very important to do considering the growing interest in entrepreneurship among students will encourage independence in doing business and not relying on other parties for work. The factors studied were Entrepreneurial Literacy, Digital Literacy and Family Experience. This study was conducted on students of the Faculty of Economics, University of Panca Marga in Probolinggo, East Java. This research method is descriptive and causal associative and takes a sample of 53 respondents, the data collection method uses a questionnaire and the sampling technique uses purposive sampling. The analytical tool used is a questionnaire test consisting of reliability test, classic assumption test, multiple regression test, determination test, hypothesis test consisting of t test, F test and dominance test. The results of the study show that Entrepreneurial Literacy, Digital Literacy and Family Experience partially and simultaneously influence entrepreneurial interest among students and family experience is the dominant factor in supporting entrepreneurial interest among students.